Disrupted emotion regulation and spontaneous neural activity in panic disorder: a resting-state fMRI study - Hai-Yang Wang; Bei-Yan Guan; Shi-Yao Wang; Ming-Fei Ni; Yan-Wei Miao; Feng Tian; Yumin Chen; Meng-Li Wu; Rui Li; Bing-Wei Zhang (SAGE Publishing, 2024)
Background: Emotional dysregulation, particularly unconscious catastrophic cognitions, plays a pivotal role in the genesis of panic disorder (PD). However, no studies have yet applied the percentage of amplitude fluctuation (PerAF) metric in resting-state functional magnetic resonance imaging to examine spontaneous neural functioning and its relation to catastrophic cognitions in PD. Objectives: To explore the interplay between resting-state neural activity, functional connectivity (FC), and unconscious emotion regulation in individuals with PD. Design: Cross-sectional study. Methods: The study encompassed 51 participants, including 26 PD patients and 25 healthy individuals. The PerAF algorithm was employed to explore the local spontaneous neural activity in PD. Regions exhibiting aberrant spontaneous neural activity were used as seed points for whole-brain FC analysis. Correlations were utilized to examine associations between local neural activity patterns and neurocognitive assessments in PD. Results: The study revealed that compared to healthy individuals, PD patients exhibited elevated PerAF values in key emotion-regulation-related brain regions, including the ventromedial prefrontal cortex (vmPFC), striatum, amygdala, dorsomedial prefrontal cortex (dmPFC), and cerebellum. In addition, the resting-state FC between vmPFC and precuneus, as well as between the cerebellum and precuneus, was weakened in PD patients. Furthermore, positive associations were noted between PerAF measurements of vmPFC and amygdala and catastrophizing scores. Conclusion: PD involves regional and network-level alterations in resting-state brain activity. The fronto-striatal-limbic circuits play a critical role in catastrophic-style emotion regulation in PD patients. Reduced FC within the default mode network and cerebellum-default mode network may signify a coordination anomaly in introspection and cognitive activities in PD. These findings complement the model of implicit emotion regulation in PD and suggest potential intervention targets.